Waste processing techniques at the landfill site using the material flow analysis method - B. Ratnawati; M. Yani; S. Suprihatin; H. Hardjomidjojo (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Waste remains an issue in tandem with the development of the local community. The quantity of waste that is stockpiled in the landfill impacts the amount of leachate, resulting in emissions and reduced landfill capacity. The main challenge for its management is choosing the most cost-effective method to minimize leachate and emissions and increase the amount of waste that is stockpiled, resulting in a longer service life of the landfill. This study aimed to select the treatment at a landfill site.METHODS: Field observations and sampling of waste composition were carried out at the Klaten Regency. Waste composition sampling was carried out over several years. Material flow analysis was used to calculate the amount of leachate, emissions, and waste in the landfills. The effectiveness and benefits of the treatment scenarios were compared.FINDINGS:  The waste consists of 55 per cent organic, 24 per cent plastic, 10 per cent paper, 3 per cent wood, 2 per cent cloth, 1 per cent glass, 1 per cent metal, and 4 per cent others. The processing scenarios were determined based on this composition. Four prospective scenarios were identified: 1) waste processing with composting; 2) composting and reuse, reduction, and recycling; 3) waste to energy; and 4) the combined process of scenarios 1 – 3. All treatments carried out can reduce leachate by 5.09 – 14.32 per cent, emissions of 11.31 – 44.48 per cent, waste 14.13 – 65.97 tons/day in the landfill, and can extend the service life of the landfill by 3 – 14 years.CONCLUSION:  Material flow analysis was used to calculate the waste processing, emission rate, and leachate production from the four processing scenarios. The reduction of leachate and emission was affected by the treatment used. Combined processing (scenario 2 or 4) can reduce leachate and emissions and extend service life. The selected processing alternative must also consider the benefit-cost ratio. Scenarios (2) and (4) have a benefit-cost ratio of more than 1, which means that the processing is feasible to implement. Scenario 4 has a higher investment cost; so, the scenario that can be applied to the Troketon landfill is scenario 2 with a small investment cost, capable of reducing polluters, extending the landfill's service life to more than 4 years, and a benefit-cost ratio of more than 1.